2022
DOI: 10.1186/s41232-022-00199-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity related to chronic pain and its modulation by microglia

Abstract: Neuropathic pain is often chronic and can persist after overt tissue damage heals, suggesting that its underlying mechanism involves the alteration of neuronal function. Such an alteration can be a direct consequence of nerve damage or a result of neuroplasticity secondary to the damage to tissues or to neurons. Recent studies have shown that neuroplasticity is linked to causing neuropathic pain in response to nerve damage, which may occur adjacent to or remotely from the site of injury. Furthermore, studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 80 publications
0
31
0
1
Order By: Relevance
“…Perhaps surprisingly, both adult neurogenesis and neuroplasticity have been reported to contribute to the maintenance of long-lasting NP (i.e., chronicity) [ 52 ] and NP that may occur adjacent to or remotely from any injury site [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps surprisingly, both adult neurogenesis and neuroplasticity have been reported to contribute to the maintenance of long-lasting NP (i.e., chronicity) [ 52 ] and NP that may occur adjacent to or remotely from any injury site [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The somatosensory cortices are located in the parietal lobe and play a pivotal role in discriminating sensory modalities and localization of sensations [ 7 , 8 ]. Although controversial [ 33 ], somatosensory cortices are known to be involved in the development and maintenance of chronic pain symptoms [ 34 ]. Multiple studies have reported changes in the somatosensory cortex following nerve injury [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported changes in the somatosensory cortex following nerve injury [ 35 , 36 , 37 , 38 ]. Animal studies have shown that pain induced by peripheral nerve injury alters neuronal activity and glial activation in the affected S1 region, leading to abnormal pain processing in the brain [ 3 , 34 ]. Conversely, mimicking these changes in S1 results in neuropathic pain-like symptoms [ 3 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible that changes in microglia phenotype might alter the neuronal function in brain regions related to pain facilitating chronic pain development. Accordingly, it has been reported that activated microglia are involved in shaping the neuroplasticity underlying chronic pain ( 178 ) and pain-associated affective disorders ( 179 ).…”
Section: “Arthritic Brain” and Pain—the Role Of Glia Cellsmentioning
confidence: 99%